EFFICIENCY OPTIMIZATION OF ATTENDANCE SYSTEM WITH GPS AND BIOMETRIC METHOD USING MOBILE DEVICES - Benfano Soewito; Echo Wahana Marciano Simanjuntak (Bina Nusantara University, 2014)
The existing attendance system still has drawbacks, namely the queue in front of the finger scanner, the attendance data are not integrated with Human Resources Systems, and also the employees who work outside the office cannot get in the attendance system to roll presence. In the other hand, everyone has the mobile devices and all the mobile devices will be embedded a finger scanner in the future. In this paper, it is proposed the absence system using one own device. The finger scanner and coordinate Global Position System (GPS) are used as inputs for the attendance system that integrated with payroll system and human resource management tools. Application base on android platform is developed because the android is the most platforms that have been using in the most mobile devices. Using our proposed methodology, the employee can roll presence using their mobile devices and the do not need to be in queue and the employees who work outside the office also can roll presence. Research showed that proposed methodology can be used for the next generation attendance system.